BOMB 14C ENRICHMENT INDICATES DECADAL C POOL IN DEEP SOIL? - Baisden W.T.; Parfitt R.L. (My University, 2007)
Studies of changes in soil organic carbon (SOC) stocks normally limit their focus to the upper 20–30 cm of soil, yet 0–20 cm SOC stocks are only ∼40% of 0–1 m SOC. Accounting for only the upper 20–30 cm of SOC has been justifiable assuming that deeper SOC is unreactive since it displays 14C-derived mean residence times of hundreds or thousands of years. The dramatic increase in the 14C content of the atmosphere resulting from thermonuclear testing circa 1963 allows the unreactivity of deep SOC to be tested by examining whether deep soils show evidence of ‘bomb-14C’ incorporation. At depths of 40–100 cm, a well-studied New Zealand soil under stable pastoral management displays progressive enrichment of over 200‰ across samplings in 1959, 1974 and 2002, indicating substantial incorporation of bomb 14C. This pattern of deep 14C enrichment—previously observed in 2 well-drained California grassland soils—leads to the hypothesis that roots and/or dissolved organic C transport contribute to a decadally-reactive SOC pool comprising ∼10–40% of SOC below 50 cm. Deep reactive SOC may be important in the global C cycle because it can react to land-use or vegetation change and may respond to different processes than the reactive SOC in the upper 20–30 cm of soil.
Keywords: CARBON CYCLE; DISSOLVED ORGANIC MATTER; MODEL; RADIOCARBON; ROOTS; SOIL DEPTH; SOIL ORGANIC MATTER; SOIL PROFILES